Pediatric pulmonary lymphatic flow Disorders: Diagnosis and management. (November 2020) - Biko, David M.; Dori, Yoav; Savoca, Melanie; Krishnamurthy, Ganesh; Smith, Christopher L.; Laje, Pablo; Rome, Jonathan J.; Escobar, Fernando
Abstract: Pulmonary lymphatic flow disorders involve the abnormal lymphatic flow via lymphatic channels to the lungs and pleural space. Plastic bronchitis and chylothorax are the main complications of this abnormal lymphatic perfusion, which has been termed pulmonary lymphatic perfusion syndrome (PLPS). Following lymphatic access, dynamic contrast MR lymphangiography is the imaging modality of choice to diagnose these disorders. Management includes medical therapy, percutaneous interventions under fluoroscopy, and surgical interventions.